Engineering tomato disease resistance by manipulating susceptibility genes - Wang, Duoduo; Mandal, Palash; Rahman, Md Sazan; Yang, Lirong (Frontiers in Genome Editing, 2025)
Various pathogens severely threaten tomato yield and quality. Advances in understanding plant-pathogen interactions have revealed the intricate roles of resistance (R) and susceptibility (S) genes in determining plant immunity. While R genes provide targeted pathogen resistance, they are often vulnerable to pathogen evolution. Conversely, S genes offer a promising avenue for developing broad-spectrum and durable resistance through targeted gene editing. Recent breakthroughs in CRISPR/Cas-based technologies have revolutionized the manipulation of plant genomes, enabling precise modification of S genes to enhance disease resistance in tomato without compromising growth or quality. However, the utilization of the full potential of this technique is challenging due to the complex plant-pathogen interactions and current technological limitations. This review highlights key advances in using gene editing tools to dissect and engineer tomato S genes for improved immunity. We discuss how S genes influence pathogen entry, immune suppression, and nutrient acquisition, and how their targeted editing has conferred resistance to bacterial, fungal, and viral pathogens. Furthermore, we address the challenges associated with growth-defense trade-offs and propose strategies, such as hormonal pathway modulation and precise regulatory edits, to overcome these limitations. This review underscores the potential of CRISPR-based approaches to transform tomato breeding, paving the way for sustainable production of disease-resistant cultivars amidst escalating global food security challenges.